Ecology of Rhodnius robustus Larrousse, 1927 (Hemiptera, Reduviidae, Triatominae) in Attalea palm trees of the Tapajós river region (Pará State, Brazilian Amazon) - Dias, Fernando Braga Stehling (2014)
Background: The rising number of acute cases of Chagas disease in the State of Pará, reported in the past two decades, has been associated, in part, with the ingestion of juice of local palm tree fruits, mainly açaí berry and bacaba. Near the study area, in Santarém, Pará State, an outbreak of Chagas disease has been notified and investigations suggest the consumption of bacaba juice as the main source of infection with T. cruzi. The purpose of this study is to assess the aspects associated to the ecology of Rhodnius robustus in palm trees of three communities of the Tapajós region, in the State of Pará, Brazil. Methods: Palm trees were cut down and dissected to search for triatomines. DNA from triatomines was extracted to investigate natural infection by Trypanosoma cruzi and T. rangeli. For statistical analyzes, data from infestation of palm trees, as well as the rates of natural infection by T. cruzi and T. rangeli were compared by Chi-square test. Triatomine density values were analyzed by the nonparametric Kruskal Wallis test and then comparisons between each pair of variables were made by the Mann–Whitney test assuming a confidence interval of 95%. Results: We dissected 136 palm trees, 60 at the end of the rainy period and 76 at the end of the dry period. Seventy-three of them (53.7%) were infested with triatomines and three species were found, namely: Rhodnius robustus, Rhodnius pictipes and Panstrongylus lignarius. We collected 743 triatomines, and R. robustus was predominant (n = 739). The identification of natural infection of the insects by trypanosomatids revealed that 125 triatomines were infected by T. cruzi, 69 by T. rangeli and 14 presented both parasites, indicating the presence of mixed infection in the same vector. Conclusion: The results suggest that São Tomé is the community with greater density of triatomines and infestation of palm trees; also, it demonstrates the existence of an intense sylvatic cycle in the region, which demands intensive surveillance to prevent human transmission.